Konsep Rusydan dalam Pendidikan Qur'ani Sebagai Solusi Edukatif terhadap Adiksi Gadget pada Generasi Z - Maulana, Alif; Isnaeni, Ahmad; Budimansyah, Budimansyah (Shautut Tarbiyah-IAIN Kendari, 2025)
Generation Z faces a serious challenge related to technology addiction, especially cell phones, which has become a major source of social and mental problems. A 2023 survey in the United States indicates that 56% of Gen Z respondents feel addicted to their phones. This situation is even more acute in Indonesia, where the average teenager spends more than 6 hours a day using gadgets, and is reported to check their phone over 100 times daily, feeling powerless to disconnect. Excessive gadget use, particularly exceeding 8 hours a day, is associated with an increased risk of sleep problems, mental disorders, and social isolation, where direct interaction is neglected in favor of virtual communication. Furthermore, the misuse of social media by children, fueled by a lack of parental supervision, low digital literacy, and emotional immaturity, increases vulnerability to cyberbullying. As a fundamental solution, this paper offers a Quranic Parenting framework, referencing Surah An-Nisa verses 5-6. The verse emphasizes the importance of evaluating intellectual maturity (rusydan) and the ability to manage wealth before transferring responsibility, which is interpreted as a guideline for parents to strengthen financial education and continuous supervision over digital device ownership.